Harmful risk factors in the work of a nurse - Depta, Adam; Strzelecka, Agnieszka; Witczak, Radosław; Arciszewska, Halina (Polish Journal of Public Health, 2013)
Introduction. Nurses are exposed to harmful and troublesome factors, as they come in contact with all sorts of dangers every day.Aim. The aim of this paper was to assess the degree of exposure of hospital nurses to harmful and troublesome factors, and to examine a relationship between selected non-measurable characteristics. Material and methods. The study was conducted among 115 randomly selected respondents employed in hospital wards of the Independent State Health Care Centre in Sieradz in April 2011. The authors of the study used a survey questionnaire. The chi-square independence test was applied to determine the dependence. The strength of this relation, if statistically significant, was examined with the C-Pearson’s contingency coefficient. Results. The respondents are aware of adverse effects of biological, physical, chemical and biopsychosocial factors. Less than 50% of the respondents are overstrained due to shift work. One hundred-and-eleven respondents from the studied group assessed their work as burdensome. They blamed physical and mental overstrain, a shortage of medical personnel and great demands for that situation. The statistical analysis showed a relationship between an increased occurrence of factors negatively affecting the osteo-articular system in the workplace and the shift work system, the shift work system of nurses and a general feeling of excessive strain, inconvenience of work and presence of factors overstraining the osteo-articular system. In the first case, the strength of this relationship was moderate, it was strong in the second case and weak in the third one. However, no correlation was observed between the occurrence of mental and physical ailments at nurses and aggression at work.Conclusions. Bearing in mind the harmful character of the studied factors we should deepen knowledge in this sphere and apply prophylaxis. Moreover, employees should be made aware of effects of a proper kind of relaxation after work and the importance of measures to prevent infections.